DETERMINATION OF CHANGE IN CONTENT OF HEAVY AND RADIOACTIVE METALS IN DRINKING WATER BY AN INDIRECT ANALYSIS METHOD BASED ON SCALE TESTS - Miloš Rajković; Mirjana Stojanović; Maja Eremić Savković; Uroš Lačnjevac; Dragan Tošković (Journal of Engineering & Processing Management, 2013)
In this paper the content of metal in drinking water was determined in two samples, one from 2008 and other from 2010, by the indirect method based on the analysis of scale, which had originally been suggested by Rajkovic and associates. Received results confirmed that drinking water according to the metal content was of constant level (metals are lower than MAC values), but with increased content of U. By the method of fraction extraction it was proved that increased content of U regarded mainly to natural U, and less to U of anthropogenic origin. The increased content of isotope 90Sr was also noticed, probably as the effect of increased presence of alkaline earth metals. The analysis structure of scale by the usage of SEM determined that the dominant form was calcium carbonate of crystal structure of hexagonal shape which corresponded to calcite. By Röentgen diffraction analysis of dust it was determined the content of calcite which contained CaO; MgO; FeO; MnO and CO2 and it belongs to medium manganese calcites. All the analyses done in this paper, confirmed that indirect method of determination of metal content had been reliable and applicable for determination of low concentrations of metals in drinking water.
Keywords: drinking water; scale; heavy metals; scanning electron microscopy; X-ray diffraction analysis ∙ Gamma-spectrometry